Paremia about the Earth in the Russian Language: Linguocultural Research - DAHKAEI, Sedigheh Kazemnejad; CHUPRYAKOVA, Olga Anatolevna; SAFONOVA, Svetlana Sergeevna; VOTYAKOVA, Irina Aleksandrovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the study of paremias as fragments of the linguistic picture of the world. The most widely used genres of paremias in russian are considered in detail - proverbs and sayings representing information about the history of the russian people, their way of life, customs, traditions, established and generally accepted system of values and moral guidelines. A detailed lexicographic analysis of the lexeme “earth” is carried out. The structure of proverbs and sayings about the land is analyzed. It is concluded that proverbs and sayings are built on the principle of syntactic parallelism. RESUMEN El artículo está dedicado al estudio de las paremias como fragmentos de la imagen lingüística del mundo. Los géneros de paremias más utilizados en ruso se consideran en detalle: proverbios y dichos que representan información sobre la historia del pueblo ruso, su forma de vida, costumbres, tradiciones, sistema de valores y pautas morales establecidos y generalmente aceptados. Se realiza un análisis lexicográfico detallado del lexema “tierra”. Se analiza la estructura de los proverbios y dichos sobre la tierra. Se concluye que los proverbios y dichos se basan en el principio del paralelismo sintáctico.